PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI MIA MA DAREL HIKMAH PEKANBARU - Fitria Nurhidayah; Maria Erna; Asmadi M.Noer (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this research is to examine applying Novick learning model to improve students’ crtical thinking skills on the subject of reaction rates. The research method used the quasi-experimental with the Randomized Control Group Pretest-Posttest Design. The population in this study were all students of class XI MIA MA Darel Hikmah Pekanbaru in 2018/2019 academic year consisted of 3 classes, and 2 classes random samples was selected, XI MIA 1 as the experimental class and XI MIA 3 as control class. The research instrument are question of reaction rate based on indicators of critical thinking skills. Based of result hypothesis test using the t-test with α = 0.05 obtained tcount> ttable (2,95> 2,02). Based on these results it can be concluded that the application of the Novick learning model can improve students' critical thinking skills on the subject of the reaction rate in class XI MIA MA Darel Hikmah Pekanbaru.Keywords : Novick learning model, critical thinking skills, reaction rates.